Hubungan Motivasi Kerja dengan Kinerja Guru Taman Kanak Kanak di Kecamatan Padang Utara Kota Padang - Fadhila Rahmi; Zulminiati Zulminiati (Jurnal Bahana Manajemen Pendidikan, 2019)
This study aims to determine the relationship between work motivation and the performance of kindergarten teachers in Padang Utara District, Padang City. The hypothesis in this study proposed is that there is a meaningful relationship between work motivation and the performance of kindergarten teachers in Padang Utara District,Padang City. This type of research correlational with a kuantatif approach,which describes the relationshipof work motivation with the performance of kindergarten teachers in Padang Utara District, Padang City. The population in this study, with 82 teacher  who taught in kindergarten in Padang Utara Subdistrict,Padang City,and were sampled in this study,with 43 people taken using the stratified Proposional Random Sampling techninque. The instruments in this study are likert scale model questionnaires that have been tested for validity and reability and the result are valid and reabel. Data were analyzed using Produt Moment correlation formula with SPPS version 17. Based on data analysis,the coefficient of determination of work motivation was obtained at 0,512. The correlation coefficient between work motivation and the performance of kindergarten teachers is 0,715.This means that motivation is 71,5% towards the performance of significant 5% kindergarten teachers. Based of these data it can be concluded work motivation has a positive relationship with the performance of  kindergarten teacher in Padang Utara District,Padang City.